Dendrochronological study of painted chests from the collection of the Gorenjska Museum in Kranj - Čufar, Katarina (Les (Ljubljana), 2020)
Painted chests are an important part of museum collections of folk art in the Alpine region. At the Gorenjska Museum in Kranj, we examined over 30 chests mostly made of Norway spruce (Picea abies) and selected 18 of them for dendrochronological analysis. We took high resolution images of the radial boards of the constructional parts of the chests for tree-ring analyses. We constructed tree-ring chronologies for each of the 18 chests. Nine of them were dendrochronologically dated (eight spruce chests and one silver fir) with the end dates ranging from 1742 to 1882. The study of the chest made of silver fir (Abies alba) is presented in detail. Half of the chests could not be dated, mainly due to the low number of tree-rings or large variability of tree-ring signal of spruce in Slovenia and consequently lack of adequate reference chronologies. The results show that dendrochronology can be used to determine age and obtain information about chests that cannot be obtained from other sources.
Keywords: Alpine area; alpski prostor; chests; cultural heritage; dendrochronology; dendrokronologija; folk art; kulturna dediščina; ljudska umetnost; museum; muzeji; navadna smreka; Norway spruce; painted furniture; Picea abies; poslikano pohištvo; skrinje